Superior high creep resistance of in situ nano-sized TiCx/Al-Cu-Mg composite - Lei Wang (Nature Portfolio, 2017)
Abstract The tensile creep behavior of Al-Cu-Mg alloy and its composite containing in situ nano-sized TiCx were explored at temperatures of 493 K, 533 K and 573 K with the applied stresses in the range of 40 to 100 MPa. The composite reinforced by nano-sized TiCx particles exhibited excellent creep resistance ability, which was about 4–15 times higher than those of the unreinforced matrix alloy. The stress exponent of 5 was noticed for both Al-Cu-Mg alloy and its composite, which suggested that their creep behavior was related to dislocation climb mechanism. During deformation at elevated temperatures, the enhanced creep resistance of the composite was mainly attributed to two aspects: (a) Orowan strengthening and grain boundary (GB) strengthening induced by nano-sized TiCx particles, (b) θ′ and S′ precipitates strengthening.